Magnetic Properties of Multisegmented Cylindrical Nanoparticles with Alternating Magnetic Wire and Tube Segments - Escrig-Murua, J; Salazar-Aravena, D; Corona-Gonzalez, R (2013)
The magnetic properties in multisegmented cylindrical nanostructures comprised of nanowire and nanotube segments are investigated numerically as a function of their geometry. In this work we report systematic changes in the coercivity and remanence in these systems. Besides, we have found the ideal conditions for a magnetic configuration with two antiparallel domains that could be used to help to stabilize magnetic nanoparticles inside ferromagnetic multisegmented cylindrical nanoparticles. This magnetic behavior is due to the fact that the tube segment reverses its magnetization before the wire segment, allowing the control of the magnetic domain walls motion between two segments. In this way, these magnetic nanoobjects can be an alternative to store information or even perform logic functions. © 2013 Elsevier B.V.